VARP and Rab9 Are Dispensable for the Rab32/BLOC-3 Dependent Salmonella Killing - Arda Balci (Frontiers in Cellular and Infection Microbiology, 2020)
Salmonella enterica serovar Typhi (S. Typhi) is the causative agent of typhoid fever, a disease that kills an estimated 200,000 people annually. Previously, we discovered an antimicrobial pathway dependent on Rab32 and BLOC-3 (BRAM) that is critical to kill S. Typhi in murine macrophages. The BLOC-3 complex is comprised of the two sub-units HPS1 and HPS4 and exhibits guanine-nucleotide exchange factor (GEF) activity to Rab32. In melanocytes, Rab9 has been shown to interact with HPS4 and RUTBC1, a Rab32 GTPase activating (GAP) protein, and regulate the Rab32-mediated melanosome biogenesis. Intriguingly, Rab9-deficient melanocytes exhibit hypopigmentation, a similar phenotype to Rab32 or BLOC-3 deficient melanocytes. Additionally, VPS9-ankyrin-repeat-protein (VARP) has been shown to regulate melanocytic enzyme trafficking into the melanosomes through interaction with Rab32. Although Rab32, Rab9 and VARP are a part of melanogenesis in melanocytes, whether Rab9 and VARP are required for the BRAM mediated killing in macrophages is currently unknown. Here we showed that HPS4 is recruited to the Salmonella-containing vacuoles (SCV) and over-expression of BLOC-3 significantly increased Rab32-positive bacteria vacuoles. We found that SCV acquire Rab9, however over-expressing Rab9 did not change HPS4 localization on bacteria vacuoles. Importantly, we used shRNA to knock-down Rab9 and VARP in macrophages and showed that these proteins are dispensable for Rab32 recruitment to the SCV. Furthermore, we assessed the survival of S. Typhimurium in macrophages deficient for Rab9 or VARP and demonstrated that these proteins are not essential for BRAM pathway-dependent killing.